The association between vitamin D consumption and gallstones in US adults: A cross-sectional study from the national health and nutrition examination survey - Chuxuan Bin; Chuan Zhang (Journal of the Formosan Medical Association)
Background: Gallstone disease is common in the US and Europe. Gallstones are associated with factors such as age, sex, weight, and serum cholesterol levels. A complex relationship exists between vitamin D levels and cholesterol metabolism. However, the relationship between vitamin D level and gallstones remains unclear. This study aimed to investigate whether gallstones are associated with dietary vitamin D (D2+D3) consumption (VDC) in American adults. Methods: This cross-sectional study used data from people who participated in the National Health and Nutrition Examination Survey between March 2017 and March 2020. Multivariate logistic regression models were used to determine the association between vitamin D intake and the presence of gallstones. Stratified and interaction analyses were performed to determine whether the relationship was stable across different subgroups. Results: 6873 participants were included. VDC (per 1 SD) was positively associated with gallstones in the crude model (OR: 1.11, 95% Confidence Interval (CI): (1.05–1.17); p < 0.001), Further adjustment did not affect the results. When vitamin D was analyzed using quartiles, with increased quartile of VDC, the incidence of gallstones increased, and the OR of Q2 (OR: 1.08, 95% CI: 0.89–1.32, p = 0.436) and Q3 (OR: 1.55, 95% CI: 1.28–1.87, p < 0.001) was higher than that of Q1 in crude model. After adjusting for covariates, there is a positive association between VDC and incidence of gallstones without statistical significance. Conclusion: VDC was positively associated with the incidence of gallstones, however, further studies are required to gather additional evidence.